Requirements for room temperature shimming of the human brain. - Clare, S; Evans, J; Jezzard, P (2006)
Room temperature (RT) shims are used routinely in MRI to remove global and local B(0) field inhomogeneity introduced by the subject. Most clinical scanners use only second-order spherical harmonic terms, but with the increasing availability of very high field systems, third- and fourth-order terms are a serious consideration. However, choosing appropriate coil strengths is of critical importance in shim coil design since overspecification of the shim strengths can lead to a variety of problems, including shim coil self-resonance. In this study B(0) field map data collected over a period of 6 months (over 400 brain volumes) were analyzed to find the characteristic B-fields required to shim these brains. These data can be used to specify the coil requirements to effectively shim the human brain.